Elementary School Students' Sports Participation Rates - Muhammad Hisyam; Agus Kristiyanto; Deddy Whinata Kardiyanto (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This study aims to analyze sports participation among elementary school students in Karanganyar Regency, with a focus on comparing participation patterns between rural and urban areas.